2007
DOI: 10.1038/sj.ijo.0803650
|View full text |Cite
|
Sign up to set email alerts
|

Human visceral adipose tissue and the plasminogen activator inhibitor type 1

Abstract: Objective: The objective of this study was to systematically evaluate the molecular basis of the association between visceral fat mass and plasma plasminogen activator inhibitor-1 (PAI-1) levels in man. Design: A comprehensive approach comprising observational, in vitro, and human intervention studies. Measurements and results:We confirmed an exclusive relationship between visceral fat and plasma PAI-1 levels (r ¼ 0.79, Po0.001) and corroborated preferential PAI-1 release from adipose tissue explants. Yet, mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
2
8
4
Order By: Relevance
“…This is in contrast with the negative correlation observed with plasma PAI-1 levels in the present study and to what we might have expected [29][30][31]. In accordance with our observations, Lindeman et al [30] found an inverse relationship between abdominal subcutaneous and visceral AT PAI-1 mRNA levels and BMI values.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This is in contrast with the negative correlation observed with plasma PAI-1 levels in the present study and to what we might have expected [29][30][31]. In accordance with our observations, Lindeman et al [30] found an inverse relationship between abdominal subcutaneous and visceral AT PAI-1 mRNA levels and BMI values.…”
Section: Discussioncontrasting
confidence: 81%
“…This is in contrast with the negative correlation observed with plasma PAI-1 levels in the present study and to what we might have expected [29][30][31]. In accordance with our observations, Lindeman et al [30] found an inverse relationship between abdominal subcutaneous and visceral AT PAI-1 mRNA levels and BMI values. In addition, Bastard et al [32] reported that PAI-1 mRNA and protein abundance in subcutaneous abdominal AT of non-diabetic obese individuals were increased following very low caloric diet induced weight loss.…”
Section: Discussioncontrasting
confidence: 81%
“…Individuals who developed T2DM also demonstrated a significant increase in waist-hip ratio, indicating that PAI-1, DM and central obesity are closely related. This is also in line with previous studies that demonstrated a significant association between PAI-1 levels and the amount of visceral adipose tissue [40]; overexpression of PAI-1 has also been observed in cultured adipocytes and in adipose tissue of mice and humans [41] strengthening the concept that (visceral) adipose tissue is an important source of PAI-1. Interestingly, PAI-1 KO mouse models on high-fat diet displayed a significant reduction in obesity, hyperglycaemia and hyperinsulinaemia compared to wild type mice fed on a similar diet [42].…”
Section: Discussionsupporting
confidence: 80%
“…Another limitation of the study could be associated with a rather high variability of A-V differences present in this as well as in other studies (22,31). When taking into account this variability we cannot rule out, that a release of some cytokines with low production in scAT could be missed.…”
Section: Discussionmentioning
confidence: 57%